(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article substantiates an integrative school-based framework for psychodiagnostics and psychocorrection of students’ thinking processes in the context of increasing cognitive demands in contemporary education. The paper interprets thinking not as a single “ability,” but as a system of interrelated processes (analysis, synthesis, comparison, generalization, inference, cognitive flexibility, and metacognitive regulation) that develop unevenly and are sensitive to learning conditions, emotional factors, and classroom interaction. The proposed framework connects three logically consistent stages: (1) multi-source psychodiagnostic assessment (screening, in-depth evaluation, and functional formulation), (2) targeted psychocorrection (strategy instruction, metacognitive scaffolding, executive-function support, and cognitive-behavioral elements), and (3) monitoring of dynamics with feedback to teachers and parents. Emphasis is placed on ethical and culturally sensitive assessment, the avoidance of rigid labeling, and the priority of developmental interpretation. The article offers a practical algorithm for school psychologists: defining the referral question, selecting tools, triangulating data, designing an individualized correction plan, and evaluating outcomes through repeated assessment. It is concluded that an integrated “diagnosis–intervention–monitoring” model can strengthen students’ reasoning, learning independence, and self-regulation while supporting inclusive and evidence-informed educational practice.